Assessing sperm whale (Physeter macrocephalus) movements within the western Mediterranean Sea through photo‐identification. Issue 1 (July 2014) - Carpinelli, Eva; Gauffier, Pauline; Verborgh, Philippe; Airoldi, Sabina; David, Léa; Di‐Méglio, Nathalie; Cañadas, Ana; Frantzis, Alexandros; Rendell, Luke; Lewis, Tim; Mussi, Barbara; Pace, Daniela Silvia; et al.
ABSTRACT The Mediterranean sperm whale sub‐population is considered 'Endangered' by both ACCOBAMS and the IUCN. Conservation policies require protected species populations to be monitored, but the distribution and movements of sperm whales across the Mediterranean Sea are still poorly understood. To provide insight into sperm whale movements, the photo‐identification catalogue from the Strait of Gibraltar was compared with seven other collections: (a) the North Atlantic and Mediterranean Sperm Whale Catalogue (NAMSC), and with photo‐identification catalogues from (b) the Alboran Sea, Spain, (c) the Balearic Islands, Spain, (d) the Corso‐Provençal Basin, France, (e) the Western Ligurian Sea, Italy, (f) the Tyrrhenian Sea, Italy, and (g) the Hellenic Trench, Greece. Of 47 sperm whales identified in the Strait of Gibraltar between 1999 and 2011 a total of 15 animals (32%) were photographically recaptured in other sectors of the western Mediterranean Sea in different years. None of the Strait of Gibraltar sperm whales were resighted in Atlantic waters or in the eastern Mediterranean basin. These results indicate long‐range movements of the species throughout the whole western Mediterranean Sea, with a maximum straight‐line distance of about 1600 km. The absence of any photographic recaptures between the Mediterranean Sea and the North Atlantic Ocean supports the genetic evidence of an isolated sub‐population within the Mediterranean Sea. Long‐term photo‐identification efforts and data sharing between institutions should be further encouraged to provide basic information necessary for the implementation of effective sperm whale conservation measures in the whole basin. Copyright © 2014 John Wiley & Sons, Ltd.